Rapid differentiation of Ralstonia solanacearum avirulent and virulent strains by cell fractioning of an isolate using high performance liquid chromatography. (January 2016) - Zheng, Xuefang; Zhu, Yujing; Liu, Bo; Yu, Qian; Lin, Naiquan
Abstract: Ralstonia solanacearum is one of the most destructive plant bacterial pathogens worldwide. The population dynamics and genetic stability are important issues, especially when an avirulent strain is used for biocontrol. In this study, we developed a rapid method to differentiate the virulent and avirulent strains of R. solanacearum and to predict the biocontrol efficiency of an avirulent strain using high performance liquid chromatography (HPLC). Three chromatographic peaks P1, P2 and P3 were observed on the HPLC spectra among 68 avirulent and 28 virulent R. solanacearum strains. Based on the HPLC peaks, 96 strains total were assigned to three categories. For avirulent strains, the intense peak is P1, while for virulent strains, P3 is the majority. Based on the HLPC spectra of R. solanacearum strains, a chromatography titer index (CTI) was established as CTIi  = Si /(S1 +S2 +S3 ) × 100% (i represents an individual HPLC peak; S1, S2 and S3 represent peak areas of P1, P2 and P3, respectively). The avirulent strains had high values of CTI1 ranging from 63.6 to 100.0%, while the virulent strains displayed high values of CTI3 ranging from 90.2 to 100.0%. Biological inoculation studies of 68 avirulent strains revealed that the biocontrol efficacy was the best when CTI1  = 100%. The purity and genetic stability of R. solanacearum strains were confirmed in the P1 fraction of avirulent strain FJAT-1957 and P3 fraction of virulent strain FJAT-1925 after 30 generations of consecutive subculture. These results confirmed that fractioning by HPLC and their deduced CTI can be used for rapid and efficient evaluation and prediction of an isolate of R. solanacearum . To the best of our knowledge, this is the first report that HPLC fractioning can be used for rapid differentiation of virulent and avirulent strains of R. solanacearum . Highlights: The HPLC characteristics of Ralstonia solanacearum strains were systematically analyzed in this study. Fractioning by HPLC can be used for rapid differentiation of virulent and avirulent strains of R. solanacearum. A chromatography titer index (CTIi ) was established to evaluate biocontrol efficiency of R. solanacearum avirulent strain.